DETERMINING THE JOB READINESS OF VOCATIONAL GRADUATES IN THE INDUSTRIAL REVOLUTION 4.0 ERA: PERSPECTIVES ACADEMICS & PRACTITIONERS - Muhammad Indra; Pardjono Pardjono; Dwi Rahdiyanta; Mochamad Bruri Triyono; Yogi Herdianto; Romy Saputra (Department of Mechanical Engineering Education, 2025)
The work readiness of vocational graduates is crucial for realizing Independent Learning and Independent Campus (MBKM (acronyms in Bahasa)). However, there are pros and cons from various parties and issues regarding the lack of readiness (competence) of vocational graduates in the 4.0 era, and few discussions about the relationship between this and MBKM. Therefore, this article aims to analyze the best practices in MBKM for the work readiness of vocational graduates in the era of the 4.0 industrial revolution by applying a quantitative survey method. The results of the study reveal that character is the dominant factor for vocational work readiness in the era of the 4.0 industrial revolution, followed by technical and non-technical competencies, with the conclusion that character and its sub-aspects, such as honesty, discipline, responsibility, hard work, a creative attitude (open to new ideas), and curiosity, are fundamental to supporting the future of vocational graduates who are able to compete globally